Ogólne zasady prawa w acquis communautaire oraz w prawie międzynarodowym publicznym - istotniejsze pytania badawcze (Studia Prawnicze / The Legal Studies, 2023)
General principles of law are considered to be a classic problem of public international law what is reflected in the literature of the subject. Nevertheless, these principles are often (wrongly) omitted or marginalized in some handbooks and monographs. On the other hand, theoretical works do not find and neither do not analyze many important aspects included in the issue. In this context the following, more important research questions appear: 1.The position of general principles of law in systems of sources of internal and international law (excluding acquis communautaire) is not clear. In internal systems legal rationalism includes to apply general principles of law, although, as a rule, these principles are not taken into account by the states’ constitutions. Such mechanisms do not work in public international law, because of particular interest of subjects, who try to understand legal norms in a way profitable for them. 2.In theory there is concordance regarding the process of forming and obtaining binding force by general principles of law and of their relations with other sources of law. 3.Does the fact that states’ constitutions very often omit general principles of law mean that they do not exist in these systems? 4.It can be supposed that even in acquis communautaire (where principles have precisely described hierarchic position) discussed principles (which are on the lowest place in the hierarchy of sources of primary law) do not have to be applied while acts of higher order are created. There are also some important remarks which we can enumerate below: 1.The role of general principles of law exposed in acquis communautaire and their impact on other sources of law as well as supremacy over national legal systems does not find wider reflection in universal, public international law, though it would be justified from legal and rational point of view. 2.Both in the international and internal law a fact of breaking (offending) the general principles of law by legal acts or decisions (as well by the procedures of creation of law) does not impose their invalidity either ex lege or on the basis of complain. 3.Art. 25 of the Fundamental Law (Constitution) of the Federal Republic of Germany is referred sometimes in the theory as contradictory to above affirmation, but it must be compared with contents of German constitutional law which doesn’t provide any mechanism of ex lege respect for treaty international law rules in the internal legal order. 4.Constitution for Europe may break or stop (profitable for binding force of public international law and for democratic harmonization of internal orders, deriving from acquis communautaire) tendency fortifying role and effectiveness of general principles of law. This work tries also to present such complicated problem as: the way of formulating of general principles of law in the international law theory and judgment, as well as in the practice of internal, international and Community orders. Great attention is also dedicated here to individual, more important of general principles of law. Concluding, we may state that general principles of law must constitute a decisive base of any legal order, as well as for its creative, functional, interactive and relative activities. Any legal order corresponding to its essential requirements (being logical, complete and non-contradictory) must not only include general principles of law but also assure their high position in hierarchy of that system. It will be also profitable to introduce these postulates to public international law and to the Union law created by Treaty establishing Cons- titution for Europe. But are there perspectives and will to carry into effect these postulates?